Trends in cause of death among patients with renal cell carcinoma in the United States: a SEER-based study - Xiangpeng Zhan; Tao Chen; Ying Liu; Hao Wan; Xiaoqiang Liu; Xinxi Deng; Bin Fu; Jing Xiong (BMC, 2023)
Abstract Background Renal cell carcinoma (RCC) survival has improved due to recent developments in RCC treatment. Therefore, other co-morbid conditions may have a more critical role. This study aims to explore the common causes of death in patients with RCC to improve the management and survival of RCC. Method We used the Surveillance, Epidemiology, and End Results (SEER) (1992-2018) database to get patients with RCC. We calculated the percentage of total deaths of six kinds of the cause of death (COD) and the cumulative incidence of death for each selected cause over survival time. The joinpoint regression was utilized to present the trend of mortality rate by COD. Results We enrolled 107,683 cases with RCC. RCC was the leading cause of death in patients with RCC [25376(48.3%)], followed by cardiovascular diseases [9023(17.2%)], other cancers [8003 (15.2%)], other non-cancer diseases [4195 (8%)], non-disease cause [4023 (7.7%)], and respiratory diseases [1934 (3.6%)]. The proportion of patients who died of RCC decreased gradually over survival time, and this value decreased from 69.71% in 1992-1996 to 38.96% in 2012-2018. The non-RCC cause mortality rate showed an increasing trend, whereas a slight decrease was observed in RCC specific mortality rate. The distribution of such conditions varied across different patient populations. Conclusion RCC was still the primary COD of patients with RCC. However, non-RCC cause death was increasingly important among RCC patients in recent two decades. Cardiovascular disease and other cancers were crucial co-morbidities that required significant attention in the management of RCC patients.